Teknik Convert Offline e-RKAM dalam Meningkatkan Akuntabilitas dan Transparansi Keuangan Madrasah di Wilayah Kabupaten Kepulauan Tanimbar - Sukriyadi, Sukriyadi; Fenanlampir, Krispina; Bulurditi, Titi wou A.; Watkaat, Andreas Jidon (SENTRI: Jurnal Riset Ilmiah, 2025)
Technology must used in Madrasahs as prepare financial accountability reports online using the e-RKAM application pivotal in 3T areas of Tanimbar Island Regency network contraints. The purpose of this study to exemine how the offline conversion technique of e-RKAM can improve the financial accountability and transparency of madrasah compare with offline conversion of RKAM. The research method uses a mixed method with a simultaneous or exploratory sequential design, starting with qualitative research obtained from observation, interviews, and documentation at madrasahs. Meanwhile, quantitative data analysis will use statistical techniques (regression). The research was conducted at 10 madrasahs (2 subdistricts, 5 villages). The research subjects consisted of 3 people (madrasah principals, treasurers). This qualitative research result revealed that the availability of the internet network is inadequate,e RKAM application online used to report Bos Funds,there is no import feature on RKAM to upload manual excel data dealing financial accounting reports but RKAM assist the operators and treasurers in reporting by offline. Thus, the accuracy and precision of financial reports can prevent fraud (misappropriation) from occurring. Therefore, the accuracy and precision of financial reports can prevent fraud that could lead to the misuse of funds in madrasahs. Meanwhile, the results of quantitative research explain the validity, reliability, and regression tests, showing that there is a significant effect of the Offline e-RKAM Technique (X) on the accountability and transparency of Bos funds (Y) if in the future the offline e-RKAM technique with Excel for Accounting is implemented in the 3T region.